Paid attention innovative advertising for a digital world - Yakob, Faris (Kogan Page, 2015)
"Rapid changes in communication technologies shifted the media environment from one of scarcity to one characterized by abundance. Advertisers are paying more and more money to reach fewer and fewer people, as audiences consume endless streams of content across different platforms. When you can no longer buy enough attention for advertising to remain efficient -- how do brands respond?Spanning communication theory, neuroscience, creativity and innovation, media history, popular culture, branding, and emerging technologies, Paid Attention explores how ideas move people and how advertising can and should change in response to changes in the communication landscape.Topics covered include: a critical look at market research, modern theories of communication, the vanishing difference between content, media, and advertising, what ideas are and how to get them, and the future of advertising. "--